El G20 y los cambios en la gobernanza global - Kim, Chi-Wook (Revista Mexicana de Política Exterior, 2022)
Since the outbreak of the U.S. financial meltdown in 2008 and the global economic crisis, the Group of Twenty (G20) has evolved into a “premier forum” for global economic governance. A new world order is clearly forming in which we will see a shift of economic power from West to East. It is in this context that Chi-Wook Kim reviews the historical background of the G20 and its implications for changing the mode of global governance. After analyzing the achievements of four rounds of G20 summits, from Washington, London and Pittsburgh to Toronto, the author concludes that the G20 faces both opportunities and challenges in terms of effectiveness, representativeness and institutionalization. As a host country of the newly regularized G20, Korea needs to play an active role in drawing up a politically feasible agenda on global financial governance. Furthermore, Korea would do well to strengthen its political base of support by building policy networks with developing countries and non-governmental organizations. Finally, Korea’s roles include strengthening the institutional capabilities and effectiveness of the G20 by coordinating conflicts of interest among member countries and ensuring their compliance with commitments.